Serial monitoring of circulating tumor DNA in patients with primary breast cancer for detection of occult metastatic disease. Issue 8 (18th May 2015) - Olsson, Eleonor; Winter, Christof; George, Anthony; Chen, Yilun; Howlin, Jillian; Tang, Man‐Hung Eric; Dahlgren, Malin; Schulz, Ralph; Grabau, Dorthe; van Westen, Danielle; Fernö, Mårten; Ingvar, Christian; et al.
Abstract: Metastatic breast cancer is usually diagnosed after becoming symptomatic, at which point it is rarely curable. Cell‐free circulating tumor DNA (ctDNA) contains tumor‐specific chromosomal rearrangements that may be interrogated in blood plasma. We evaluated serial monitoring of ctDNA for earlier detection of metastasis in a retrospective study of 20 patients diagnosed with primary breast cancer and long follow‐up. Using an approach combining low‐coverage whole‐genome sequencing of primary tumors and quantification of tumor‐specific rearrangements in plasma by droplet digital PCR, we identify for the first time that ctDNA monitoring is highly accurate for postsurgical discrimination between patients with (93%) and without (100%) eventual clinically detected recurrence. ctDNA‐based detection preceded clinical detection of metastasis in 86% of patients with an average lead time of 11 months (range 0–37 months), whereas patients with long‐term disease‐free survival had undetectable ctDNA postoperatively. ctDNA quantity was predictive of poor survival. These findings establish the rationale for larger validation studies in early breast cancer to evaluate ctDNA as a monitoring tool for early metastasis detection, therapy modification, and to aid in avoidance of overtreatment. Synopsis: Serial measurement of circulating tumor DNA (ctDNA) is shown to be a robust and accurate occult metastatic disease biomarker in patients diagnosed with primary breast cancer. Measured ctDNA levels are a quantitative risk factor for poor outcomes. A combination of low‐coverage whole‐genome sequencing with personalized droplet digital PCR, analytical methods, and a bioinformatics pipeline was developed for quantification of ctDNA in blood plasma samples collected during clinical follow‐up of patients with primary (non‐metastatic) breast cancer. ctDNA analysis can discriminate patients with eventual metastasis from those with long‐term disease‐free survival with 93% sensitivity and 100% specificity (ROC area 0.98, P  = 0.001). ctDNA‐based detection of occult metastatic disease preceded clinical detection for 86% of patients by an average 11 months and in some cases by 3 years. No ctDNA could be detected at any time‐point after surgery for patients with long‐term disease‐free survival. The level of ctDNA was a quantitative risk factor for clinical metastatic disease (logistic regression odds ratio 2.1 for each doubling of ctDNA levels, P  = 0.02) and death (odds ratio 1.3 per ctDNA doubling, P  = 0.04). Abstract : Serial measurement of circulating tumor DNA (ctDNA) is shown to be a robust and accurate occult metastatic disease biomarker in patients diagnosed with primary breast cancer. Measured ctDNA levels are a quantitative risk factor for poor outcomes.